Periradicular lesions in HIV-infected patients attending the faculty of dentistry: clinical findings, socio-demographics status, habits and laboratory data - seeking an association (Clinics, 2014)
OBJECTIVE: The purpose of this study was to estimate the prevalence of periradicular lesions in HIV-infected Brazilian patients and to assess the correlation of several factors with the periradicular status. METHOD: One hundred full-mouth periapical radiographs were evaluated. A total of 2,214 teeth were evaluated for the presence of periradicular lesions, caries lesions, coronal restorations, pulp cavity exposure and endodontic treatment. RESULTS: The prevalence of periradicular lesions was 46%. There were no significant differences between individuals with or without periradicular lesions with respect to their socio-demographic status, habits, laboratory data and route of HIV infection. However, the presence of a periradicular lesion was statistically correlated with the number of teeth with endodontic treatment (p = 0.018), inadequate endodontic treatment (p = 0.025), images suggesting pulp cavity exposure (p = 0.002) and caries lesions (p = 0.001). CONCLUSIONS: The prevalence of periradicular lesions in HIV-infected individuals was 46% and was not related to HIV infection.